Pathways to reduce CO2 emissions as countries proceed through stages of economic development. (June 2019) - Valadkhani, Abbas; Nguyen, Jeremy; Bowden, Mark
Abstract: We propose a new approach to identify pathways for countries to reduce carbon dioxide emissions (CO2 ) per capita through possible changes in their energy consumption portfolio. Utilizing data from the last half century (1965–2017) for 79 countries, we investigate how changes in the composition of primary energy consumption (i.e. oil, coal, gas and renewables) can contribute to changes in per capita CO2 emissions, depending on the time-varying level of individual countries' real per capita income. To this end, threshold panel regressions (with common and fixed effects) are estimated to endogenously determine an unknown number of possible pathways (delineated by break points) to reduce emissions. This study provides important policy insights into the effects of switching from one source of primary energy consumption to another on per capita emissions, as nations progress through stages of economic development. Such relative costs can be compared and contrasted (a) across country groupings, (b) through time, as real per capita income changes, and (c) with those of other country groupings that fall within similar per capita income brackets. Highlights: We examine the effects of oil, coal, gas and renewable consumption on CO2 emission. We use panel data for 79 countries during the last half century (1965–2017). We examine the effects of different types of energy sources on CO2 emissions. Renewables reduce CO2 emissions when economies reach a certain income threshold. As real per capita income rises, countries can use oil and coal more efficiently.